THE EFFECT OF FEATURE VIDEO ON THE ABILITY OF PRE-SERVICE TEACHERS TO APPRECIATE INDONESIAN TRADITIONAL ARTS - Karsono; Joko Daryanto; Rukayah (Universitas Muhammadiyah Ponorogo, 2018)
This paper is the research result that aimed to determine the effect of video-feature learning media on the ability of pre-service elementary school teachers to appreciate Indonesian traditional arts. The research method used was true experiment with a between-subject design (two experiment control group design). The population of this study was 600 students of elementary school teacher education at a university in Surakarta with a sample of 120 students assigned to the experimental and control groups. The sampling technique used was random sampling. The instrument validity used content validity and construct validity to test the validity of test instruments and media. The data were collected using tests and interviews. They were then analysed using t-test with SPSS 16 for windows. The results of the study showed that there is a difference in the ability to appreciate arts between the students in the control and experimental groups. This can be seen from the mean pre-test score of the experimental class of 13.727 which experienced an increase from the initial test (pre-test) of 10.045. On one hand, the mean post-test score of control class was 9.909 which experienced a slight increase from the mean of the initial test (pre-test) of 9.818. The conclusion of this study is that the video-feature media influences the ability of the pre- service teachers of elementary school teacher education program.